Analysis of impact toughness and the critical stress intensity factor KIc in ferrite-austenite welded joints with different heat input - Bukvić, Aleksandar G.; Petrović, Dalibor P.; Radisavljević, Igor Z.; Dimitrić, Saša S. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: Constructions always have several critical points that can be sources of possible defects. All these critical places must be taken into account in safety assessment where the most unfavorable exploitation factors are considered and the local safety of a joint is assessed. Today, joints of various compositions are becoming more frequent in metal constructions. Due to the requirements of economy and ecology, welded joints of microalloyed ferritic steels with high-alloyed austenitic steels are increasingly encountered during the construction of power plants, chemical facilities, etc. Tests of such welded joints have been performed on tanks for oil derivatives, where parts of the tank shell are made of microalloyed ferritic steel and the roof structure is made of high-alloyed austenitic steel. Methods: In the paper, an experimental analysis of crack propagation in an austenitic-ferritic welded joint was performed. The welding was performed by the MIG welding process with two different heat inputs, and the same filler material MIG 18/8/6 was used. Two types of welded plates were tested. the characteristics of the base, filler and auxiliary materials and welding technologies are given. Notched test specimens with an initiated crack-type fracture were made in order to determine the impact properties and fracture mechanics parameters. The results: The research carried out within this study aimed to compare the obtained results of the impact toughness and fracture toughness at flat deformation in a ferrite-austenitic welded joint. An evaluation of the results obtained during the testing of the experimental plates welded with different amounts of heat input is also given. Conclusion: These test results established the dependence of the geometry of a propagating crack and the stress conditions for further crack propagation. It is possible to determine the values of the parameters that describe the behavior of the material, both in linear-elastic and in elasto-plastic fracture mechanics.